Genetic Association With Pseudomonas aeruginosa Acquisition in Cystic Fibrosis: Influence of Surfactant Protein D and Mannose-Binding Lectin - Nourkami-Tutdibi, Nasenien; Freitag, Klemens; Zemlin, Michael; Tutdibi, Erol (Frontiers in Immunology, 2021)
Background: Pseudomonas aeruginosa (PA) infection in cystic fibrosis (CF) is associated with poor prognosis. Surfactant protein-D (SFTPD) and mannose-binding lectin (MBL) play a critical role in innate immunity and response to bacterial infections. We investigated serum levels and genetic variants of SFTPD and MBL in CF patients. Method: 35 Caucasian patients homozygous for ΔF508del were genotyped for functional relevant polymorphisms within MBL2 (promoter -221 Y/X, codons 52, 54 and 57) and SFTPD genes (Met11Thr, Ala160Thr, Ser270Thr). Serum levels of collectins, clinical characteristics and PA status were correlated with genetic data. Results: Patients age, gender and PA status did not affect MBL and SFTPD serum concentrations. MBL concentrations were correlated with MBL haplotypes. Patients with chronic Pseudomonas aeroginosa infection (PAC) and MBL insufficiency had a shorter interval between first PA infection and onset of PAC (0·01 vs. 4·6 years, p<0·04) as well as a lower median age at transition to PAC (9·8 vs. 16·4 years, p<0·03) compared to MBL sufficient patients with PAC. SFTPD serum level and FEV1% (Spearman r=-0·41, p<0·03) showed a negative correlation irrespective of PA infection status. The hazard ratio to PA acquisition was increased in carriers of the SFTPD haplotype 11Thr-160Ala-270Ser compared to carriers of the common 11Met-160Thr-270Ser haplotype (HR 3·0 [95%CI: 1·1-8·6], p<0·04). Conclusion: MBL insufficiency leads to a shorter interval between first PA infection and onset of chronic infection. Susceptibility to PA acquisition is associated with SFTPD genetic variants with 11Thr-160Ala-270Ser as risk haplotype for early PA infection. This may be due to presence of threonine associated with oligomeric structure of SFTPD and binding ability to bacteria.